PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DIMEDIASI OLEH BUDAYA ORGANISASIONAL DAN PEMBERDAYAAN TERHADAP PEMBELAJARAN ORGANISASIONAL (Studi Kasus SMP Negeri Di Kecamatan Ulujami Kabupaten Pemalang) - Edi Topan, 1352020036; Liana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study examines the Influence of Transformational Leadership Mediated by Organizational Culture and Organizational Learning Empowerment against (Case Study Ulujami Junior High School in the District Pemalang). The population in this study were teachers Ulujami Junior High School in the District Pemalang totaling 125 people. In this study, using primary data obtained by questionnaire. The research method approach statistical program SPSS (Statistical Package for Social Science). The results showed that transformational leadership has no influence on organizational learning. Organizational culture mediates the effect of transformational leadership on organizational learning. Empowerment mediates the influence of transformational leadership on organizational learning.Keywords: Transformational Leadership, Organizational Culture, Empowerment, Learning Organisasional